SMARCB1-deficient and SMARCA4-deficient Malignant Brain Tumors With Complex Copy Number Alterations and TP53 Mutations May Represent the First Clinical Manifestation of Li-Fraumeni Syndrome. (22nd September 2022) - Hasselblatt, Martin; Thomas, Christian; Federico, Aniello; Nemes, Karolina; Johann, Pascal D.; Bison, Brigitte; Bens, Susanne; Dahlum, Sonja; Kordes, Uwe; Redlich, Antje; Lessel, Lienhard; Pajtler, Kristian W.; et al.
Abstract : Atypical teratoid/rhabdoid tumor (AT/RT) is a malignant central nervous system tumor predominantly affecting infants. Mutations of SMARCB1 or (rarely) SMARCA4 causing loss of nuclear SMARCB1 or SMARCA4 protein expression are characteristic features, but further recurrent genetic alterations are lacking. Most AT/RTs occur de novo, but secondary AT/RTs arising from other central nervous system tumors have been reported. Malignant gliomas, IDH wild-type, arising in patients with Li-Fraumeni syndrome typically show somatic mutations of TP53 as well as complex copy number alterations, but little is known about the loss of SMARCB1 or SMARCA4 protein expression in this context. Here, we report 2 children in whom malignant supratentorial brain tumors with SMARCB1 deficiency, complex copy number alterations, and somatic TP53 mutations lead to the discovery of pathogenic/likely pathogenic TP53 variants in the germline. Screening of the molecularneuropathology.org dataset for cases with similar genetic and epigenetic alterations yielded another case with SMARCA4 deficiency in a young adult with Li-Fraumeni syndrome. In conclusion, SMARCB1-deficient or SMARCA4-deficient malignant brain tumors with complex copy number alterations and somatic TP53 mutations in children and young adults may represent the first clinical manifestation of Li-Fraumeni syndrome and should prompt genetic counseling and investigation for TP53 germline status.